Single sheets of graphene for fabrication of fibers with enhanced mechanical properties. Issue 40 (7th October 2021) - Salim, Muhammad G.; Thimons, Luke A.; Kim, Min A.; Carr, Brennan; Montgomery, Michelle; Tolman, Nathan; D. B. Jacobs, Tevis; Liu, Haitao
Abstract : This paper reports the fabrication and mechanical properties of macroscale graphene fibers (diameters of 10 to 100 μm with lengths upwards of 2 cm) prepared from a single sheet of single-layer graphene grown via chemical vapor deposition (CVD). Abstract : This paper reports the fabrication and mechanical properties of macroscale graphene fibers (diameters of 10 to 100 μm with lengths upwards of 2 cm) prepared from a single sheet of single-layer graphene grown via chemical vapor deposition (CVD). The breaking strength of these graphene fibers increased with consecutive tensile test measurements on a single fiber, where fiber fragments produced from a prior test exhibited larger breaking strengths. Additionally, we observed an overall reduction of surface folds and wrinkles, and an increase in their alignment parallel to the tensile direction. We propose that a foundation of this property is the plastic deformations within the fiber that accumulate through sequential tensile testing. Through this cyclic method, our best fiber produced a strength of 2.67 GPa with a 1 mm gauge length.